2014
DOI: 10.5301/ejo.5000449
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Different Types of Gas-Permeable Contact Lenses in Keratoconus and Their Visual Results

Abstract: We detected an increase in VA in patients with rigid contact lenses. In addition, some contact lenses were better tolerated by patients and were used for a longer time during the day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
6
2
Order By: Relevance
“…In this study, aspherical-curve HCLs were used for stages 3 and 4. Kazanci et al reported poorer BCVA outcomes than those in our study [ 17 ]. Our aspherical-curve HCLs may have achieved better BCVA than those in previous studies because of the larger eccentricity (E) values in the peripheral-zone curve design, resulting in a good HCL fit ( Table 7 ).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In this study, aspherical-curve HCLs were used for stages 3 and 4. Kazanci et al reported poorer BCVA outcomes than those in our study [ 17 ]. Our aspherical-curve HCLs may have achieved better BCVA than those in previous studies because of the larger eccentricity (E) values in the peripheral-zone curve design, resulting in a good HCL fit ( Table 7 ).…”
Section: Discussioncontrasting
confidence: 81%
“…In previous studies on multi-curve HCLs, the HCLs were not designed to have a flat peripheral zone curve; however, the BCVA, duration of HCL wear, and HCL wearing success rates were better than those obtained in this study [ 17 19 ]. The reason for the poor result of multi-curve HCLs in our study may be that most multi-curve HCLs were used for stage 4 cases.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Contact lens are the primary form of visual correction for patients with keratoconus [16]. In a large lens trial for keratoconus, it was observed that aspheric RGP was preferred by patients wearing lenses 4-8 hours/day, but Rose K was reported to have wearing time more than 8 hours a day [17]. In our patient, his wearing habit of keratoconus RGP contact lens was 8 to 9 hours in a day.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, they use aspheric surfaces to coincident to the ectatic cornea, with increased lens diameters up to 10.00 or 11.00 mm. The fitting of large diameter lenses is becoming more complicated though, because, it could lead to the areas of increased unwanted pressure on the cornea [ 59 - 60 ].…”
Section: Contact Lenses In Keratoconusmentioning
confidence: 99%